(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: Audits carried out in the health field have helped hospital managers to improve patient care and control costs. Objective: Mapping non-conformities in glosses pointed out by the billing sector of a private hospital. Method: Quantitative descriptive and retrospective documentary study; based on gloss reports from a private hospital in the Mid- Northern Mato Grosso State. The Data refer to the period from January to December 2017. Descriptive analysis, frequency and percentage calculation were performed Microsoft Office Excel 2007® software for data tabulation and treatment purposes. Results: There was prevalence of technical glosses. Glosses regarding medical staff comprised: lack of medical report, as well as of records concerning patient evolution, hospital discharge, performed procedures signature and stamping in expense sheets and drug prescriptions; Glosses regarding the nursing staff comprised: lack of check and stamp on medical, and nursing prescriptions, on material and medication using, and non-registration of performed procedures (higher prevalence for puncture/bandages). Gloss amount led to losses that could have been invested in in order to improve the institution itself. Conclusion: It is necessary training these professionals about the important role play by notes in medical records, minimum data standardization and forms to report patients’ evolution, and about research on workload and organizational culture. It is essential emphasizing that health institutions must invest in training teams capable of managing the quality and safety of care provided to patients.